(untitled) (Academicia Globe: Inderscience Research, 2022)
The purpose of our research is the directed synthesis of high sulfate hydroaluminate in the composition of the hardening products of slag-alkali binders based on blast-furnace or electro-thermophosphorus slag and alkali metal compounds forming the Na20-Na2S04-Ca0-Al203-Si02-H20 system, studying the structure and phase composition over time expanding and stressing slag-alkali cement, determination of the physical and mechanical properties of the binder.